Mobilidade intergeracional qualificada: uma abordagem de mensuração utilizando regressões quantílicas - Silva, Ana Cláudia Annegues da (2014)
This study aims to empirically analyze the intergenerational income mobility in the light of this concept. For this, two empirical tests are performed with education of parents and children data in Canada and Brazil. The methodological procedure consists of: 1) estimate the relationship between the schooling of children and parents and 2) analyze the behavior of the error of the regression through the socioeconomic status of the parents; is expected to reduce the error variance for parents with more education. We opted also by the method of quantile regression, given the problem of identification of model, pointed out by Figueiredo, Lima e Schaur (2014), present in the estimations by least squares. The results showed that in Canada the education of parents has significant influence on the education of children. Furthermore, it was found that the qualified mobility is verified, since the error variance is negatively related to parents' education. The results for Brazil show increasing variance with the level of parental education, so that the intergenerational mobility did not correspond the characteristics of a qualified mobility.